A arte contemporânea e a Abordagem Triangular: conexões possíveis para o ensino de Artes Visuais - Mauro Roberto Vieira (2018)
This article has as its objective to reflect about my experiences as an artist teacher of contemporary Art in a public school in the city of Betim, Minas Gerais. I describe and discuss these experiences in connection with the Triangular Approach a system developed by the teacher and researcher Ana Mae Barbosa in the 80’s decade with the purpose of elaborating a pedagogical proposal for the teaching/learning process of Art for the final years of Elementary School.